Meta-analyses between 18 candidate genetic markers and overweight/obesity - Tang, Linlin (BioMed Central, 2014)
AIMS: The goal of our study is to investigate the associations between 18 candidate genetic markers and overweight/obesity. METHODS: A total of 72 eligible articles were retrieved from literature databases including PubMed, Embase, SpingerLink, Web of Science, Chinese National Knowledge Infrastructure (CNKI), and Wanfang. Meta-analyses of 18 genetic markers among 56,738 controls and 48,148 overweight/obese persons were done by Review Manager 5.0. RESULTS: Our results showed that SH2B1 rs7498665 polymorphism was significantly associated with the risk of overweight/obesity (overall odds ratio (OR) = 1.21, 95% confidence interval (CI) = 1.09-1.34, P = 0.0004). Increased risk of overweight/obesity was also observed in FAIM2 rs7138803 polymorphism (overall OR = 1.11, 95% CI = 1.01-1.22, P = 0.04). CONCLUSION: Our meta-analyses have shown the important role of 2 polymorphisms (SH2B1 rs7498665 and FAIM2 rs7138803) in the development of overweight/obesity. This study highlighted the importance of above two candidate genes (SH2B1 and FAIM2) in the risk of overweight/obesity. VIRTUAL SLIDES: The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/2785487401176182.